The use of mixed methods to identify typology of poverty in East Java, Indonesia - Doddy Sumbodo Singgih; Sudarso Sudarso; Siti Mas'udah (Jurnal Sosiologi Dialektika, 2020)
This article describes the results of concurrent mixed method testing to identify the typology of poverty in one particular area in East Java, Indonesia known as the "Madura Horseshoe". So far, typology studies of poverty in Indonesia use a single research method. The use of concurrent mixed methods is rarely done and even considered taboo in conventional research. The test results show that the method is very suitable to academic needs and very comprehensive in identifying the typology of poverty, particularly rampant poverty in an exclusive area with specific social structure and culture, namely those dominated by a particular ethnic group. The test concludes that the typology of poverty in the exclusive region of "Madura Horseshoe" is, in majority, a structural typology. The residents suffer from poverty because they do not have productive assets and social networks. Only a small percentage has cultural constraints, of which problems, including poverty, are solved by means of praying to God and asking blessings of sustenance. If this does not yield, they give up and resign to predestined fate.